Lived Experience of Online Teaching During the COVID-19 Pandemic: Implications for Curriculum and Teaching - Khanal, Peshal (Interdisciplinary Research in Education, 2021)
As the COVID-19 pandemic has affected all sphere of human life and the schools across the country are closed due to the risk of spreading the virus, online teaching has become a major alternative pedagogical strategy among the private schools in particular. This article reports a study that explores how private school teachers perceive and adopt technological learning, how they transfer their technological knowledge and skills into the online classroom and how they self-assess their practices. This is done through a phenomenological study focusing on the meaning the participants make from their lived experience on ‘technological learning and application’ in the face of the pandemic. The study found that dealing with uncertainty and fear of the COVID-19 and the additional pressure for doing online teaching amidst the crisis evoked frustration and anguish among the teachers. Despite a number of challenges and crisis, teachers, however, learn to deal with the technological challenges and manage to run the class through virtual mode. Nevertheless, they assess the online delivery is not effective due to the various constraints. The study suggests for ensuring the access of ICT resources and facilities to both teachers and students, sufficient training to the both groups and digitalize curricular materials for the effective implementation of virtual learning.